The Impact of the Applied Demonstration Strategies on Learning Referee Signals for Female Basketball - Zainab Abdul Sadah Ali Marhoon; Ayman Hani Abdul-Jabburi; Mustafa Adil Alwan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Our research aims to: Preparing exercises for the applied demonstration strategies in learning referee signsin female basketball. Knowing the effect of the applied demonstration strategies on learning referee signalsin female basketball. The researchers have used the experimental design with equal groups, as the researchcommunity included the second stage students who are (24) female students for the academic year 2018-2019, that they were randomly divided (lots) into two groups by (12) female students, after that, educationalunits were prepared, using the application strategies as exercises were applied for 8 educational units. Theresults were extracted and the appropriate statistical treatments were used to reach the results. In light of theresults, the researchers reached the following:1- The applied demonstration strategies had an effective role in learning the referee signals basketball forfemale students.2- Using the strategies, save the effort and time for the teacher and the student in learning the referee signalsin the basketball for the students well, which it is suitable for teaching this category.3- The use of the applied demonstration strategies has a positive impact on the interaction of female studentsduring the exercise and their attendance.